A review on self-healing polymers and polymer composites for structural applications - Cioffi, M. Odila H. [UNESP]; Bomfim, Anne S. C. [UNESP]; Ambrogi, Veronica; Advani, Suresh G. (Wiley, 2022)
Polymer composites when employed for structural applications undergo dynamic stresses and strains that initiate fatigue-induced microcracks, which by their coalescence cause the failure of the materials, thus limiting their service life. To overcome this hurdle, one of the recent approaches relies on the development of smart self-healing polymers that, analogously to biological systems, can use damage as a trigger to activate the self-repair phenomenon, thus extending their service life. This work reviews the self-healing approach in polymer-based materials for structural applications. It focuses on three main aspects, which are also explained with schematics that illustrate the mechanisms involved. The first aspect describes the different strategies adopted for self-healing polymeric structures, the self-healing agents used, as well as the reactions responsible for repairing the damage. The second part is focused on the methods used to disperse the self-healing agents and catalysts within the polymer systems. The third section details the different self-healing mechanisms and the effectiveness of self-healing approaches in terms of mechanical and dynamical-mechanical behavior of materials. Challenges and future research outlook highlighting the importance of relaxation time and fatigue characterization and to understand the mechanisms and possible improvements are also presented.
Keywords: autonomous healing; healing mechanism; molecule interpenetration network; self-healing agent; self-healing composites